Effectiveness of Foot Intensive Exercise Training for Subjects with Chronic Ankle Sprain: Experimental Study. - Rajkumar, Rochelle; Anitha A.; Ramana K.; Kamalakannan M. (Indian Journal of Physiotherapy & Occupational Therapy)
Background: This study was developed to determine the effectiveness of Foot Intensive Exercise Training among subjects with Chronic Ankle Sprain. Purpose: To determine the effect of Foot Intensive Exercise Training and Proprioception Exercise Training in subjects with Chronic Ankle Sprain. Materials and Methods: Thirty subjects with Chronic Ankle Sprain were divided randomly into two equal groups. "Foot Intensive Exercise Group" received plyometric exercises while the Control Group received proprioception exercises on alternate days for 6 weeks. Cumberland Ankle Instability Tool (CAIT) and Y-Balance Test were used to evaluate subjects at two intervals (Pre-Treatment and Post-Treatment). The entire process was performed from November 2022 to March 2023. Result: Statistical analysis of Cumberland Ankle Instability Tool and Y-Balance Test post values revealed constantly significant differences, with the p value of <0.0001. Conclusion: Foot Intensive Exercise is effective and increases functional ankle stability and decreases episodes of giving away in subjects with chronic ankle sprain.